Telaah Muatan Mitigasi Bencana Geologi dalam Peraturan Daerah RTRW Kabupaten Boalemo Tahun 2025–2045 - Cinta Mutia Panto; Rikarni Taruk Tiku; Moh Rifay Ahmad; Anastasya Putri Bengga; Sri Maryati; Ronal Hutagalung (Universitas Negeri Gorontalo, 2026)
This study examines the zoning and spatial use directives for geological hazard-prone areas in the Regional Spatial Plan of Boalemo Regency for 2025–2045. The study is important because spatial planning documents should function not only as development guidance but also as an instrument for geological disaster mitigation. This research used a qualitative descriptive approach with content analysis of the Boalemo Regency Spatial Planning Regulation document and supporting scientific literature. The analysis focused on three aspects: the existence of geological hazards in the spatial plan, the regulatory depth of zoning and special provisions, and the relationship between settlement allocation and potential geological vulnerability. The results show that geological disaster mitigation has been accommodated in a general way through protected areas, disaster evacuation systems, and disaster risk programs. However, the regulation has not yet explicitly classified geological hazard zones or firmly regulated non-buildable areas. This indicates that the regional spatial plan still requires stronger integration of geohazard mitigation to support safe long-term regional development.